Politik Hilirisasi Kelapa Sawit Indonesia - Gris Sintya Berlian (Jurnal Transformasi Global, 2015)
Abstract             The main objective of this research is to explore the politics of downstream palm oil industry in Indonesia which focuses on analyzing domestic factors. Those factors hold an important role in influencing the development that is considered not optimal.  Methodologically, this research is using qualitative data analysis technique through data collected from literature study and doing interviews with government officials and association in related industry for about six months. The result of this study based on institutionalist political economy perspective indicates that incapability of the government as entrepreneur and manager of conflicts causes the development of Indonesian palm oil. As an entrepreneur, government incapability can be seen from the vision of palm oil industry which is unclear. Besides, there is no synergy between government and related agents in choosing instrument for the development of the industry. As a manager of conflicts, government incapability can be seen from its unclear solution for different perspective during development of downstream palm oil industry in Indonesia. Keywords: Downstream palm oil industry, PPO, Indonesia, government, entrepreneur, manager of conflicts, policy